2016
DOI: 10.1111/ele.12577
|View full text |Cite
|
Sign up to set email alerts
|

How accessible are coral reefs to people? A global assessment based on travel time

Abstract: The depletion of natural resources has become a major issue in many parts of the world, with the most accessible resources being most at risk. In the terrestrial realm, resource depletion has classically been related to accessibility through road networks. In contrast, in the marine realm, the impact on living resources is often framed into the Malthusian theory of human density around ecosystems. Here, we develop a new framework to estimate the accessibility of global coral reefs using potential travel time f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
144
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(153 citation statements)
references
References 60 publications
7
144
2
Order By: Relevance
“…This study advances recent findings that anthropogenic impacts in terrestrial and marine systems are strongly determined by distance from cities (20) or market access (12)(13)(14). Our research therefore also contributes to evidence (7) refuting assertions that urbanization and resulting rural depopulation in the forested tropics will reduce harvesting impacts on biodiversity (32,33).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study advances recent findings that anthropogenic impacts in terrestrial and marine systems are strongly determined by distance from cities (20) or market access (12)(13)(14). Our research therefore also contributes to evidence (7) refuting assertions that urbanization and resulting rural depopulation in the forested tropics will reduce harvesting impacts on biodiversity (32,33).…”
Section: Discussionsupporting
confidence: 81%
“…Marine defaunation shadows have been observed around urban markets, in the form of market proximity-dependent declines in target seafood species, or even whole fish communities (11)(12)(13)(14). Tropical inland fisheries have also been overexploited (8), yet evidence is based on local effects of rural-subsistence fishing (8,15), so the impacts of overfishing inland waters to supply urban markets are unclear.…”
mentioning
confidence: 99%
“…The human influence metric does not take account of resource abundance metrics, such as reef area, nor of human infrastructure and travel time, or livelihood alternatives such as agriculture and animal husbandry among other socioeconomic attributes that should influence fishing pressure . Given the better predictions of human influence and environmental factors in other regions (Friedlander et al 2003, Brewer et al 2013, Houk & Musburger 2013, Williams et al 2015, Maire et al 2016, Mellin et al 2016a, the weaker responses found here suggests the need for an evaluation of fishing pressure and the factors that promote it at smaller spatial scales. Good models must account for various local factors influencing the balance between fish production and human impacts.…”
Section: Environmental Habitat and Human Influencesmentioning
confidence: 78%
“…Biomasses in the high human influence areas were composed of taxa of low fisheries or economic value, including small damselfish and odd-shaped piscivores such as lizardfish, cornetfish, scorpionfish, and trumpetfish. Human influence and related variables have been shown to be good predicators of fish biomass and vulnerable taxa in some regions (Brewer et al 2013, Maire et al 2016) but such variables may be a crude metric of human impacts because of variations in the responses of target and non-target taxa and whether or not fishers are migratory (McClanahan & Muthiga 2017). The human influence metric does not take account of resource abundance metrics, such as reef area, nor of human infrastructure and travel time, or livelihood alternatives such as agriculture and animal husbandry among other socioeconomic attributes that should influence fishing pressure .…”
Section: Environmental Habitat and Human Influencesmentioning
confidence: 99%
“…At the same time, species at higher trophic levels are disproportionally affected by human activities such as fishing, with potentially severe consequences for ecosystem functioning (Pauly et al 1998;Estes et al 2011). Overfishing of predators is a common ailment of many coral reefs around the world, yet the consequences of this on ecosystem functions remain poorly understood (Mumby et al 2012;Fenner 2014;Maire et al 2016). The release of the corallivorous crownof-thorns starfish (Acanthaster planci, Linnaeus, 1758) from predation pressure, for example, is believed to have contributed to pervasive outbreaks and large-scale coral mortality on Indo-Pacific reefs (Jackson et al 2001;Baird et al 2013).…”
Section: Introductionmentioning
confidence: 99%